The regeneration of the Tagaytay City Public Market for responsible food waste management - Leung, Aira Pauline D. (College of Architecture, University of the Philippines Diliman, 2019)
The thesis project aims to explore how a public market's redevelopment can incorporate food waste management, as a response to the persisting food loss at the retail-consumer level of our value supply chain. Tagaytay City Public Market was chosen as the site of research because of its namesake's strong market culture, environmental agenda, and need for alternative and accessible waste treatment methods. With goals of redeveloping the public market, diverting food waste and creating an enclosed food waste management loop, a regenerative approach was applied. Anaerobic digesters, a regenerative form of waste treatment technology, was integrated in the redevelopment, since it transforms organic waste into profitable products in a compacted system that is simple to operate. As for the architecture, the market's redevelopment was coined as a regeneration, where viable components of the old market were used in creating a new market that enjoins people to act on food waste issues. This inadvertently attempts to reduce construction waste, paralleling the diversion of food waste. Additions to the typical market programming consists of spaces that serve as contact points to the waste management facilities, whether it be through environmental reward or as an outlet for the products of the digester. Overall, the layouts of the spaces take advantage of Tagaytay's naturally cool climate in order to create a comfortable environment, not only for the benefit of the human users but for the preservation of the perishable goods of the market as well, given the limitations of its typology. In condclusion, responsible food waste management was defined as recognizing food waste as an economic loss, as a social responsibility and as a form of resources that can be used to create something new. Applying this mindset to the redevelopment of a public market utilizes the traditional role of the market as a central node in a community, in bringing people closer to waste management issues, enjoining people to become aware and do their part.